Valproic acid mediates miR-124 to down-regulate a novel protein target, GNAI1. (December 2015) - Oikawa, Hirotaka; Goh, Wilson W.B.; Lim, Vania K.J.; Wong, Limsoon; Sng, Judy C.G.
Abstract: Valproic acid (VPA) is an anti-convulsant drug that is recently shown to have neuroregenerative therapeutic actions. In this study, we investigate the underlying molecular mechanism of VPA and its effects on Bdnf transcription through microRNAs (miRNAs) and their corresponding target proteins. Using in silico algorithms, we predicted from our miRNA microarray and iTRAQ data that miR-124 is likely to target at guanine nucleotide binding protein alpha inhibitor 1 (GNAI1), an adenylate cyclase inhibitor. With the reduction of GNAI1 mediated by VPA, the cAMP is enhanced to increase Bdnf expression. The levels of GNAI1 protein and Bdnf mRNA can be manipulated with either miR-124 mimic or inhibitor. In summary, we have identified a novel molecular mechanism of VPA that induces miR-124 to repress GNAI1. The implication of miR-124→GNAI1→BDNF pathway with valproic acid treatment suggests that we could repurpose an old drug, valproic acid, as a clinical application to elevate neurotrophin levels in treating neurodegenerative diseases. Highlights: VPA induces miR-124, which in turn, down-regulates GNAI1 to activate cAMP and increase in BDNF. We have shown GNAI1's role in BDNF regulation and GNAI1 could be used as a biomarker to improve prognosis in neurodegenerative patients. Since VPA is already a commonly prescribed anti-epileptic and mood stabilizer, we propose its use in neurodegenerative diseases.